Vila Waldemar Rodrigues: preservando parte da história das habitações populares relacionadas a viação férrea - Santa Maria, RS. - Denardin, André de Siqueira (2017)
Until the end of the 19th century, the Brazilian habitational politics were almost null, only from the 20th century on, after countless trials to solve the set of problems, which involved the basic habitation, was established the practice of the production of housing for rent and the workers villages. The institutes and the pension funds, together with the retirement funds, were the firsts entities to give support to the basic habitation production. In these fittings, the research verifies the historical, urbanistic and architectonical information from the Vila Waldemar Rodrigues, sited in the city of Santa Maria, meaningful modern set, built in 1960, with connection to the railroad network, which finds itself still conserved, whole and active. The protection of this heritage is the starting point of this study, which verifies the necessary connection of the urban sprawl with the so-called “ Railway Spot”, where is not perceived the separation of the function and the consolidated social space. It is possible to rewrite the history, through the study of the urban layout and the architectonical work. Revealing the behavior of one determined society, showing the needs and yearnings common to a period or region. Turning this way, the practical knowledge of the form, of the materiality, of the function and the building technics, causing a study focused on the existing heritage.